Second Generation Patient Specific Total Knees Demonstrate a Higher Manipulation Rate Compared with “Off-the-shelf” Implants - Haeder, Paul R.; Chong, Alexander C.M.; Bhargava, Tarum (Kansas Journal of Medicine, 2019)
Introduction. Patient specific total knee arthroplasty (TKA) theoreticallyprovides a more accurate fit to the native knee but mayhave difficulty achieving full range of motion (ROM) post-operatively.Post-operative ROM data were compared between patientswho underwent cemented patient-specific cruciate-retaining(PSCR) and standard cemented posterior-stabilized (SPS) TKAs.Methods. PSCR and SPS TKAs that were performed from January2014 to September 2015 by the same surgeon using the same postoperativeprotocols at two selected facilities were reviewed. Twoandsix-week post-operative ROM data were obtained and thenumber of patients with knee flexion less than 110° was recorded.Results. Twenty-one patients in the PSCR group and 57 patientsin the SPS group were included. The percentage of patientswith knee flexion less than 110° was similar in both groups preoperatively(10% vs 14%, p = 0.60) and two-week post-operatively(57% vs 68%, p = 0.35). However, at six-week post-operativelythere was significant difference (29% vs 7%, p = 0.01).Conclusions. These results provide evidence to alert orthopaedicsurgeons when using these patient specific implants versus conventionalTKA methods. Patients whose TKA was performed usingpatient specific cutting guides struggled to obtain 110° of kneeflexion. Close monitoring, aggressive physical therapy, and earlymanipulation are recommended when using patient specific cuttingguides and custom total knee implants. Further evaluation ina larger group of patients is warranted. KS J Med 2016;9(4):88-92.